2022
DOI: 10.3390/cells11030387
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Gonadotropin Receptors in Sexual Development of Medaka

Abstract: The gonadotropins, follicle-stimulating hormone (FSH) and luteinizing hormone (LH), are secreted from the pituitary and bind to the FSH receptor (FSHR) and LH receptor (LHR) to regulate gonadal development in vertebrates. Previously, using fshr-knockout (KO) medaka (Oryzias latipes), we demonstrated that FSH regulates ovarian development by elevating estrogen levels. However, the lhr-KO phenotype in medaka is poorly characterized. Here, we generated lhr-KO medaka using the transcription activator-like effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…In addition, the fact that SP males are still able to reproduce suggests that spermatogenesis may not be completely dependent on gonadotropins, and that other factors could compensate for low gonadotropin levels. This hypothesis is consistent with previous knockout studies in male medaka, which demonstrated that the loss of fshb or lhb (46) or double knockout (KO) of fshr and lhr (47,48) does not disrupt spermatogenesis. In male zebrafish, although testis development is delayed significantly, Fsh-deficient fish are still fertile (49).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the fact that SP males are still able to reproduce suggests that spermatogenesis may not be completely dependent on gonadotropins, and that other factors could compensate for low gonadotropin levels. This hypothesis is consistent with previous knockout studies in male medaka, which demonstrated that the loss of fshb or lhb (46) or double knockout (KO) of fshr and lhr (47,48) does not disrupt spermatogenesis. In male zebrafish, although testis development is delayed significantly, Fsh-deficient fish are still fertile (49).…”
Section: Discussionsupporting
confidence: 93%
“…Although the endocrine system plays crucial role in these processes, the exact mechanisms involved in the sexual maturation of fish remain poorly understood. Studies focused on featuring gonadotropin receptors (fshr and lhr) have been recently carried out to help better understanding the role played by them in regulating sex steroid hormones and testicular development in several fish species (Maugars and Schmitz, 2008;Burow et al, 2020;Kitano et al, 2022).…”
Section: Differential Gene Expression Pattern and Plasma Sex Steroids...mentioning
confidence: 99%
“…A majority of these dysfunctions can be overcome by synthetic or pharmacological stimulation of the receptor in question. In fish, loss of function of FSHR causes masculinization and suppression of ovarian development in female medaka, whereas LHR knockouts were observed to stop ovulation 5, 6 . Recent studies leveraging advances in in silico methods and the availability of whole-crystal structures of GTHRs 7, 8 have greatly increased our understanding of GTH-GTHR binding mechanism and activation.…”
Section: Introductionmentioning
confidence: 99%